Socioeconomic and self-care profile of adolescent pregnant women (Research, Society and Development, 2020)
Early pregnancy is seen as a public health problem, this situation has repercussions worldwide and is no different in Brazil. The study aimed to identify the socioeconomic and self-care profile of pregnant adolescents. It was a descriptive, quantitative and transversal study. 185 pregnant adolescents attended at the prenatal service in Caxias-MA participated in this study. Regarding the guidelines on self-care, the research showed that most participants receive these guidelines, 138 (75%), however, what draws attention is the fact that health professionals are not the greatest advisors, but guidance from family members 51 (37%). From the data obtained, it was noted that pregnant adolescents were in situations of vulnerability, both socioeconomically and in their obstetric aspects, since early menarche and the beginning of sexual intercourse favor an early and often unwanted pregnancy.